2011
DOI: 10.1504/ijmassc.2011.042961
|View full text |Cite
|
Sign up to set email alerts
|

The influence of relational orientation on Chinese consumers' responses towards apparel mass customisation

Abstract: This study examined the impact of a Chinese cultural value, relational orientation, on Chinese consumers' responses towards mass customisation of apparel. Relational orientation, which stresses the conformity to group norms, was found to moderate the relationships between mass customisation and several aspects of consumers' perceived value. Specifically, relational orientation negatively affected perceived economic value and enjoyment from apparel mass customisation by Chinese consumers. It also negatively aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
1
Order By: Relevance
“…Specifically, it had a greater impact on the relationship between customer involvement and the freedom of co-creation than the relationship between customer involvement and the degree of collaboration. This finding was complementary to the results of Song and Fiore's (2011) study that customer relational-motivational orientation moderated the relationships between customer perception of mass customization and perceived enjoyment in the Chinese context. Song and Fiore (2011) suggested that Chinese customers of high-level relational orientation were less likely to perceive enhanced enjoyment from mass customization.…”
Section: Discussioncontrasting
confidence: 80%
“…Specifically, it had a greater impact on the relationship between customer involvement and the freedom of co-creation than the relationship between customer involvement and the degree of collaboration. This finding was complementary to the results of Song and Fiore's (2011) study that customer relational-motivational orientation moderated the relationships between customer perception of mass customization and perceived enjoyment in the Chinese context. Song and Fiore (2011) suggested that Chinese customers of high-level relational orientation were less likely to perceive enhanced enjoyment from mass customization.…”
Section: Discussioncontrasting
confidence: 80%